The Influence of Regulatory Policy, Technology Infrastructure, and Human Resource Quality on Economic Growth in Surabaya City - Sutono, Sutono; Harsono, Iwan; Nasruddin, Nasruddin; Judijanto, Loso (West Science Journal Economic and Entrepreneurship, 2023)
Economic growth of a city is a multifaceted phenomenon that is influenced by various factors, including regulatory policies, technological infrastructure, and the quality of human resources. This quantitative analysis investigates these determinants in the context of Surabaya City. Through surveys data analysis, we use Structural Equation Modeling with Partial Least Squares (SEM-PLS) to examine the relationship between regulatory policy, technological infrastructure, human capital quality, and economic growth. Our results show a significant positive relationship between these factors and economic growth, providing insights that can guide policymakers, business leaders, and academics in advancing the economic prosperity of Surabaya City.